Heparanase contributes to psoriatic lesions through crosstalk with IL-17 pathway - Chengyao Zhu; Yunqin Ren; Hongliang Yao; Bo Feng; Lunfei Liu; Min Zheng (Wolters Kluwer Medknow Publications, 2023)
Psoriasis is a chronic inflammatory disease that is considered by a network of immunocytes and cytokines. Among all, Th17 cells-derived IL-17 is a critical driving factor in the pathogenesis of psoriasis. Recently, disruption of the extracellular matrix was found to be related to psoriasis progression. In the present study, we aimed to investigate the role of heparanase (HPSE) in psoriasis and the crosstalk with the IL-17 signalling pathway. Skin tissues from non-affected areas and psoriatic lesion areas before and after 12 weeks of IL-17 monoclonal antibody treatment of 30 psoriasis patients were collected. HaCaT cells were treated with different concentrations of IL-17 antibody, and HPSE in cells and medium were measured with Western blotting assay as well as enzyme-linked immunosorbent assay (ELISA). In the imiquimod (IMQ)-induced psoriasis model, IL-17 protein and mRNA expression levels were measured, and changes in the proportion of Th17 cells were detected via flow cytometry. Our data showed that HPSE is upregulated in lesion tissues isolated from psoriasis patients, and was inhibited by anti-IL-17 treatment. In cutaneous cells and IMQ-induced psoriasis model, IL-17 promoted the synthesis of HPSE. Inversely, HPSE was also found to increase the percentage of Th17 cells derived from CD4+ T cells. Finally, we found that the combined treatments of HPSE inhibitor and IL-17 monoclonal antibody produced therapeutic effects on IMQ-induced psoriasis model. Our findings revealed the new role of HPSE in the pathogenesis of psoriasis and also provided a target for combined treatment of psoriasis.